Promises, challenges, and realities of a design-based approach to e-portfolios - Kyza, Eleni A. (My University, 2008)
Electronic portfolios can be powerful learning tools, whose process of construction can offer its creator insights into their own learning, by engaging them in knowledge construction and reflection. Even though reflection can be facilitated through the use of e-portfolios it cannot be taken for granted, with several examples in the literature citing problems with productive reflective thinking. Most of the literature on e-portfolios has focused on the use of such tools in teachers' professional development. In this context, in spite of the frequent mentions of how portfolios can create opportunities for reflection, the concept has remained ill-defined, resulting to problems in assessing it, supporting it and designing for it. In this paper, we examine how a design-based approach to e-portfolios can support middle-school students' reflective learning in science. We present a webbased tool designed to support students' reflective inquiry in science and explain how the e-portfolio features can support students' ongoing inquiry investigations. Data from a study with thirteen pairs of 6th grade students using this e-portfolio tool are used to illustrate the main affordances of the tool in supporting sense-making and reflection. The data sources included pre- and post-tests assessing students' conceptual understanding of the investigation they were solving, all the artifacts created using the web-based portfolio, and videotaped discussions of three of the pairs. Findings provide evidence that this approach supported students in their learning by structuring the students' task and offering them tools for reflection; challenges and areas of future work are also identified. This work contributes to addressing to what we see as two gaps in the existing eportfolio literature: a) the lack of extensive literature on the use of e-portfolios to support the moment-by-moment learning of younger learners; b) offering functional definitions of reflection, at a level that will be informative to design and teaching. The findings provide support for the role of e-portfolio tools in supporting learning as it unfolds, but also highlight the need for additional foci in e-portfolio research.
Keywords: E-Portfolios; Inquiry; Reflection; Science learning; Web-based tools